Policy Implications From Algorithmic Profiling and the Changing Relationship Between Newsreaders and the Media - Helberger, Natali (Javnost-The Public, 2016)
The news media are experimenting with new ways of engaging with the audience, and the use of algorithmic profiling and targeting is an important element of this strategy. The personalised newspaper is no longer only a vision from science fiction novels but is becoming a reality. The resulting shift from public information intermediary to personal information service creates new dynamics but also new imbalances in the relationship between the media and their users. The objective of this article is to explore how exactly this shift affects the relationship between the news media and news users, and what the implications are for media law and policy. More specifically, the article will argue that there is a need to conceptualise what this author calls “ fair media practices”; that is, values and principles that should guide the relationship between the media and users, and the way media content is presented and marketed to users with the help of algorithms.